Traction on the septum during transoral septotomy for Zenker diverticulum improves the final outcome. (25th April 2019) - Provenzano, Luca; Salvador, Renato; Cutrone, Cesare; Capovilla, Giovanni; Moletta, Lucia; Nicoletti, Loredana; Costantini, Mario; Merigliano, Stefano; Valmasoni, Michele
Abstract : Objective: Transoral diverticulostomy/septotomy has become a popular treatment for patients with Zenker diverticulum (ZD). To improve the results of transoral stapler‐assisted septotomy, a modification of the technique has been introduced. In this study, we aimed to compare the final outcome of such a modified transoral septotomy (MTS) with the results of traditional transoral septotomy (TTS) in patients with ZD. Methods: Fifty‐two consecutive patients with ZD underwent transoral stapler‐assisted septotomy between 2010 and 2018. Symptoms were recorded and scored using a detailed questionnaire. Barium swallow, endoscopy, and manometry were performed before and after the procedure. Results: Of the 52 patients forming the study population (male:female = 35:17), 25 had TTS and 27 had MTS. The patients' demographic and clinical parameters were similar in the two groups. No intraoperative mucosal lesions were detected, and the mortality was nil. The median time taken to complete the procedure was 25 minutes (interquartile range [IQR]: 22–35) for TTS, and 30 minutes (IQR: 25–36) for MTS ( P < 0.07). The median follow‐up was 69 months (IQR: 46–95) in the TTS group and 30 months (IQR: 25–35) in the MTS group. All patients in both groups had an improvement in their symptom score after the procedure, but the failure rates were 32% (8 of 25) after TTS and 3.7% (1 of 27) after MTS ( P < 0.02). At univariate and multivariate analyses, the procedure was the only predictor of a positive final outcome. Conclusion: Albeit with the intrinsic limitations of the study (retrospective, different time window, and different follow‐up), traction on the septum during transoral septotomy improves the final outcome of this treatment in patients with ZD. Level of Evidence: 4 Laryngoscope, 130:637–640, 2020